Psychoeducation: Utilizing psychological first aid to prevent adolescent suicide - Annas Fitria Saadah; Ainurizan Ridho Rahmatulloh; Nanda Yunika Wulandari (Universitas Muhammadiyah Magelang, 2023)
The incidence of suicide cases among teenagers is on the rise in Indonesia. The purpose of this community service is to offer psychoeducation as a form of psychological first aid to prevent suicide cases among adolescents. The partners for this initiative are students from SMAN 1 Pengasih. Community service activities involve providing psychoeducation and training to prepare them as peer counselors. Initial assessments revealed that participants had an interest in suicide cases but lacked the initial knowledge and skills required to address suicide-related issues. The outcome of this activity is that participants have gained knowledge about recognizing signs of suicidal tendencies, an understanding of what can and cannot be done in cases of suicide, and have acquired first-aid skills to support peers with suicidal tendencies. The knowledge and skills acquired by the students in dealing with the issue of suicide can prove invaluable in preventing suicide cases among adolescents.